Analysis of the influence of plyometric training in improving the performance of athletes in rhythmic gymnastics - Agostini, Barbara Raquel (2017)
Rhythmic gymnastics (RG) athletes need high-performance training since a high degree of precision is required in their exercises. Plyometric training (PT) has been used to improve athletes' neuromuscular function, explosive performance and strength in competition. The object of this study was to assess the efficiency of PT in improving the performance of RG athletes in the juvenile and adult categories over 12 months, by incorporating PT into two training macrocycles. Thirty athletes were selected; they were divided randomly into a control group (CG) and an experimental group (EG) of 15 athletes each. Two 6-month training macrocycles were drawn up for the EG in which they maintained normal training with the addition of PT. The CG maintained its normal training. Three tests were used for the assessment: vertical jump, horizontal jump and agility, assessed at 5 different moments. After 12 months it was observed an improvement in test performance in both groups, with a more significant improvement in the EG when compared to the CG. The addition of PT to normal training improved the performance of athletes by developing greater power in the lower limbs, increasing their capacity in vertical jump, horizontal jump and agility.